Thermally induced suppression of interchain interactions in dilute aqueous solutions of conjugated polyelectrolyte rotaxanes and their analogues - Tregnago, G; Afshar, A; McDonnell, SO; Anderson, HL; Cacialli, F (AIP Publishing, 2017)
We use steady-state and nanosecond time-resolved photoluminescence spectroscopy to investigate the evolution of packing interactions in dilute solutions of a sulfonated poly(diphenylenevinylene) lithium salt and its cyclodextrin-threaded polyrotaxanes as a function of the threading ratio (TR) when increasing the temperature from 10 to 40 °C. Contrary to the expectation of a temperature-induced increase of packing and aggregation, supported by previous Raman studies identifying a temperature-induced reduction in the inter-phenyl torsion angles, we find clear spectral (photoluminescence blue-shift and narrowing) and dynamic (shorter lifetimes and reduced weight of the long-lived components) signatures of a reduction of interchain interactions for the polyelectrolytes at higher temperatures with TR up to 1.3.